Methods for solid phase extraction using porous monoliths
By fixing the free three-dimensional porous column in the heat shrinkable pipe and using the flow in the fluid conduit for solid phase extraction, the problem of low extraction efficiency of target compounds in complex samples in the prior art is solved, and efficient, fast, simple and repeatable micro extraction is achieved, which is suitable for the analysis needs of the "omics" field.
Patent Information
- Application Number
- JP2024552039
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-01
- Filing Date
- 2023-02-27
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art is difficult to achieve efficient, fast, simple and repeatable micro-extraction of target compounds in complex samples, especially in the field of "omics" with small sample size and fast analysis speed.
Using a solid phase extraction method combining a free three-dimensional porous column with a heat shrinkable pipe, the sample is passed through the column by fixing the porous column in the fluid conduit, and the sample is passed through the column by flowing the fluid in the conduit, thereby achieving the extraction of the target compound.
The efficient, fast, simple and repeatable micro-extraction of the target compound is achieved, suitable for the small sample size and fast analysis requirements in the "omics" field without pre-concentration.
Smart Images

Figure 2025507869000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for the solid phase extraction of one or more compounds of interest using a porous monolith incorporated into a fluid conduit. The present invention also relates to a method for incorporating a porous monolith into a tube made from a heat shrinkable material. [Background technology]
[0002] Extraction of one or more compounds of interest from a complex mixture is essential to enable their subsequent use, in particular their identification and / or quantification. The quality of the extraction of the compound(s) of interest greatly influences the quality of the results subsequently obtained.
[0003] Currently, several methods exist for extracting the compound(s) of interest.
[0004] A practical and efficient means of carrying out the extraction consists in moving a solution containing the molecules of interest through a solid phase. For this, it is necessary to have a fluid circuit incorporating a porous material with a cross section perfectly adapted to the conduit in which it is incorporated and fixed, in order to ensure that the solution moving in the circuit inevitably passes through the porous material.
[0005] Among the materials that can be used as solid phases for extraction, porous monoliths, especially those with hierarchical porosity (HPM), exhibit advantages such as good permeability, porosity, and tunable surface chemistry. The production of devices for extraction in a miniaturized format is a challenging task.
[0006] Nema et al., Talanta, 82 (2010), 488-494, Application of Silica-Based Monolith as Solid Phase Extraction Cartridge for Extracting Polar Compounds from Urine, Ma, X., Zhao, M., Zhao, F. et al., Application of Silica-Based Monolith as Solid-Phase Extraction Sorbent for Extracting Toxaphene Congeners in Soil,J. Sol-Gel Sci. Technol.,80, 87-95 (2016), and Jorge C. Masini et al., Porous Monolithic Materials for Extraction and Preconcentration of Pollutants from Environmental Waters, Trends in Environmental Analytical Chemistry, Volume 29, 2021, e00112, ISSN As described in the paper by 2002-02-2214-1588, one of the methods for integrating HPMs into a fluid circuit consists of embedding them in the syringe body, in particular by forced insertion. This is achievable only for HPMs that exhibit sufficient resistance to the manual embedding stresses, in particular a width of several millimeters.
[0007] Another method for encapsulating HPM for SPE or chromatographic applications, as described in JP 2003-166983, consists of using a heat-shrinkable tube that shrinks onto the HPM when heated for 10 minutes at 100° C., encapsulating the HPM and holding it in place. This method is commonly used for encapsulating porous monoliths with a width of a few mm. However, for porous monoliths with small diameters, especially those with a diameter of 2 mm or less, it has been established, in particular in US Pat. No. 7,291,383, that the encapsulation described in the above-mentioned Japanese patent application is unable to preserve both the integrity of the HPM and the tightness of the incorporation.
[0008] Such extraction devices, including HPMs with large widths, require several hundreds of microliters to be moved over the HPM. They work with flow rates obtained by creating an air vacuum at the outlet of the device or by centrifugation. They are therefore not very flexible and difficult to control precisely. Moreover, they do not always meet the constraints of certain fields, especially the "-omics" fields including proteomics, metabolomics or glycomics, in terms of the reduced amount of sample, the small volumes of samples to be analyzed, and the speed required.
[0009] To miniaturize such systems, a solution proposed in particular by US Pat. No. 7,291,383 and the paper by Jorge C. Masini et al., Porous Monolithic Materials for Extraction and Preconcentration of Pollutants from Environmental Waters, Trends in Environmental Analytical Chemistry, Volume 29, 2021, e00112, ISSN 2214-1588, is to form the HPM in situ in capillaries with an inner diameter of less than 1 mm. The resulting capillaries contain, in particular, the morphology described in Bruns, S., Mullner, T., Kollmann, M., Schachtner, J., Holtzel, A. and Tallarek, U.(2010), Confocal Laser Scanning Microscopy Method for Quantitative Characterization of Silica Monolith Morphology, Analytical Chemistry,82 (15), As shown in the paper by 6569-6575, a gradient of porosity exists, which impairs reproducibility, and scanning electron microscope images very often show, on the one hand, an incomplete fixation of the HPM in the capillaries, which releases interstitial spaces that can impair the reproducibility, indeed even the quality, of the extraction by creating preferential paths, and, on the other hand, that for identical formulations, different capillary diameters do not have similar structures, which means that greater modifications are made to the initial composition but also to the method steps compared to those carried out for larger free-standing monoliths, especially to limit edge effects in the capillary walls, which makes the preparation of such capillaries long and complex, leading to structural variability.
[0010] WO 2005 / 072164 describes a monolith integrated into a polyethylene tube by inserting the monolith into the tube, heating the assembly until the tube is in a molten state, enclosing the monolith, and finally cutting the ends to allow the movement of fluids within the porous monolith. WO 2008 / 112702 describes a system including a porous monolith integrated into a support by heating the support and shrinking it onto the porous substrate. This document describes in more detail the insertion of a porous monolith with a diameter of 1.2 mm into a borosilicate glass tube with an internal diameter of 1.8 mm, heating the assembly at a temperature of 850° C. to melt the glass and shrink it onto the monolith, and then cutting the assembly to obtain a part usable for chromatography. Putting the tube into a molten state means that the molten material penetrates the pores of the porous monolith over the entire surface of the porous monolith. It is therefore necessary to cut the assembly again to allow access to the porous part of the monolith. Such cuts make the use of the assembly more complicated, especially in terms of connections, and may damage the porous monolith, especially in the case of small diameter monoliths.Furthermore, the use of small diameter monoliths is complicated in the risk that the pores of the monolith are filled during the melting of the tube material, due to the penetration of the tube material into the pores of the monolith, thereby clogging the porous monolith. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] JP 2003-166983 A [Patent Document 2] U.S. Patent No. 7,291,383 [Patent Document 3] International Publication No. 2005 / 072164 [Patent Document 4] International Publication No. 2008 / 112702 [Non-patent literature]
[0012] [Non-Patent Document 1] Nema et al., Talanta, 82 (2010), 488-494, Application of Silica-Based Monolith as Solid Phase Extraction Cartridge for Extracting Polar Compounds from Urine [Non-Patent Document 2] Ma, X., Zhao, M., Zhao, F. et al., Application of Silica-Based Monolith as Solid-Phase Extraction Sorbent for Extracting Toxaphene Congeners in Soil, J. Sol-Gel Sci. Technol.,80, 87-95 (2016) [Non-Patent Document 3] Jorge C. Masini et al., Porous Monolithic Materials for Extraction and Preconcentration of Pollutants from Environmental Waters, Trends in Environmental Analytical Chemistry, Volume 29, 2021, e00112, ISSN 2214-1588 [Non-Patent Document 4] Bruns, S., Mullner, T., Kollmann, M., Schachtner, J., Holtzel, A. and Tallarek, U. (2010), Confocal Laser Scanning Microscopy Method for Quantitative Characterization of Silica Monolith Morphology, Analytical Chemistry,82 (15), 6569-6575 [Non-Patent Document 5] Sophie Cholet et al., N-Glycomics and N-Glycoproteomics of Human Cerebrospinal Fluid, Current Proteomic Approaches Applied to Brain Function, 127, Humana Press, 360 p., 2017, Neuromethods, 978-1-4939-7119-0 978-1-4939-7118-3 [Non-Patent Document 6] Reiding et al., Anal.Chem., 86, 5784-5793 (2014), High-Throughput Profiling of Protein N-Glycosylation by MALDI-TOF-MS Employing Linkage-Specific Sialic Acid Esterification Summary of the Invention [Problem to be solved by the invention]
[0013] Thus, there is a need to have available a method for extracting compounds of interest from reduced volume samples that is simultaneously simple, rapid, efficient and highly reproducible. [Means for solving the problem]
[0014] The present invention provides a method for solid phase extraction of one or more compounds of interest from a liquid sample, comprising the steps of: - incorporating the free-standing porous monolith into a fluid conduit such that the free-standing porous monolith is fixed within the fluid system during the method to form a filter within the fluid system; - passing the sample through the porous monolith in the fluid conduit at least once over at least a portion of the porous monolith; Including, This need is met by a method in which a free-standing porous monolith has a maximum dimension across a conduit of 3 mm or less.
[0015] The term "forming a filter" is understood to mean that the liquid traversing the fluid conduit passes through the porous monolith over at least part of its length, in particular over its entire length, the "length" being defined as the largest dimension along the axis of the fluid conduit. The dimensions of the porous monolith, less than or equal to 3 mm, make it possible to process very small volumes of samples, which is particularly advantageous in certain fields, but also allows for rapid and robust processing. This also makes it possible to optimize the subsequent analysis of the extracted compounds of interest by reducing the need for preconcentration of the compounds before analysis.
[0016] The use of porous monoliths makes it possible to have a versatile device with very good extraction efficiency, since the porosity characteristics and surface chemistry of the porous monolith can be easily adapted to the type of extraction desired.
[0017] Methods for forming monoliths Preferably, the porous monolith is formed by a sol-gel process. The term "sol-gel process" refers to a process in which the precursor is a compound of the formula M(OR) n , R'-M(OR) n-1or even sodium silicate or titanium colloids, where M is a metal, transition metal or metalloid, in particular silicon, R or R' is an alkyl group and n is the oxidation degree of the metal. In the presence of water, hydrolysis of the alkoxy (OR) groups occurs, forming small particles, generally less than 1 nanometer in size. These particles aggregate to form clusters that remain in suspension without settling, forming a sol. The increase in the clusters and their condensation increases the viscosity of the medium, forming what is called a gel. The gel can continue to develop in an ageing phase, during which the polymer network present in the gel becomes denser. The gel then shrinks by expelling the solvent outside the formed polymer network, during a phase called syneresis. The solvent then evaporates during a "drying" phase, resulting in a solid material of porous glass type that gives rise to a porous monolith. The syneresis and drying phases may be simultaneous.
[0018] Preferably, the free-standing porous monolith comprises: - forming a sol comprising a sol-gel precursor in an aqueous solution, and preferably further comprising a pore former; - at least partially filling a chamber and at least one mold contained within the chamber with a previously formed sol, the mold including at least one opening that opens into the sol after filling with the sol; - forming a sol-gel matrix in a chamber starting from a sol, - removing the mold from the chamber together with the sol-gel matrix contained therein; and - removing the sol-gel matrix from the mold; - forming a porous monolith starting from the sol-gel matrix removed from the mould; The method includes the steps of: The formation of the sol, the sol-gel matrix, and the porous monolith is carried out by the sol-gel process.
[0019] The presence of at least one opening in the mold below the sol level after filling allows the filling of the mold with the sol during the filling stage and the fluid transfer of the sol between the sol contained in the mold and the sol contained in the chamber during the continuation of the method. Creating a large sol-gel matrix in the chamber and removing therefrom the part contained in the mold as the matrix is formed makes it possible to overcome the edge effect that appears in the above-mentioned method by creating a sol-gel matrix in a receptacle of always the same size. Such a method makes it possible to produce free-standing porous monoliths with similar textural properties over a wide diameter range without reoptimizing, indeed without modifying, the formulation of the initial mixture. It is also possible to obtain a great variety of monolith shapes and aspect ratios, as well as a controlled, varied and reproducible internal structure. The structure obtained is particularly uniform, thus ensuring homogeneity of resistance to mechanical stresses. This can prove useful, for example, to prevent breakage of the monolith when pressure is applied to it when it is incorporated into a fluid conduit, in particular when it is enclosed in a heat-shrinkable fluid conduit.
[0020] The sol may be formed by stirring the sol-gel precursor, preferably the solution comprising the sol-gel precursor and the pore former, for a period of time, in particular, of 5 minutes or more, more preferably of 10 minutes or more, even more preferably of 15 minutes or more. The duration of the stirring may be 3 hours or less, more preferably of 2 hours or less. During the stirring, the temperature may be controlled at a substantially constant predetermined value, in particular 0°C to 90°C, more preferably 0°C to 50°C.
[0021] The filling can be performed without the presence of air bubbles and / or gradients in the chemical composition and / or temperature of the sol within the chamber and mold.
[0022] The formation of the sol-gel matrix may include condensation to form a gel, and optionally at least partial aging to densify the gel.
[0023] Preferably, forming the sol-gel matrix in the chamber does not include drying the sol-gel matrix.
[0024] The formation of the sol-gel matrix can be carried out in the chamber and in the mold as well. The overall porosity and pore size are preferentially substantially homogenous within the chamber and the mold.
[0025] The removal of the mold and the matrix it contains from the chamber may include removing the block of sol-gel matrix containing the mold from the chamber and removing the mold and the sol-gel matrix it contains from the previously removed block. The removal of the or each mold from the block may be performed by cutting the sol-gel matrix flush with the corresponding mold or by breaking the sol-gel matrix surrounding the mold. Alternatively, the removal of the or each mold and the matrix it contains can be performed by removing the sol-gel matrix surrounding the corresponding mold after the above-mentioned removal of the block or directly in the chamber without prior removal of the block, especially if the corresponding mold is only partially immersed in the sol-gel matrix.
[0026] The removal of the sol-gel matrix contained in the or each mold can be carried out by a controlled pressure on said sol-gel matrix, for example by direct pressure by a solid having smaller dimensions than the mold, or by the pressure of a gas at a controlled flow rate, or by opening the or each mold, in particular by cutting the or each mold, or by separating the two parts of the or each mold from each other. The mold may also be in the form of two parts that are movable together, in particular separable, or movable relative to each other by a hinge.
[0027] The mold containing the sol-gel matrix may be immersed in a liquid at the stage of removing the sol-gel matrix contained in the mold, which makes it easier to remove the sol-gel matrix.
[0028] The method for producing a porous monolith may comprise, after removal of the mold from the chamber and before the formation of the porous monolith starting from the sol-gel matrix of the mold, a controlled generation of mesoporosity in the sol-gel matrix in order to form a sol-gel matrix with hierarchical porosity. The controlled generation of mesoporosity may be carried out by immersing the sol-gel matrix, removed or not removed from the mold or each mold, in an aqueous solution for the generation of mesoporosity, which contains an agent for dissolving the sol-gel matrix and / or a precursor of an agent for dissolving the sol-gel matrix. The dissolving agent may be, for example, ammonium hydroxide, sodium hydroxide or hydrofluoric acid at a concentration of 1 M or a mixture thereof. The precursor of the agent for dissolving the sol-gel matrix may be urea or a compound with an amide function, in particular formamide, acetamide, N-methylformamide (NMF) and mixtures thereof. Preferably, the concentration of the solubilizer and / or solubilizer precursor is such as to allow localized dissolution of the sol-gel matrix or matrices so as to form mesopores therein or therebetween without dissolving the sol-gel matrix or matrices entirely.
[0029] Formation of the porous monolith can include at least partial aging to densify the sol-gel matrix, especially if aging was not previously performed completely.
[0030] The formation of the porous monolith may, where appropriate, include drying the sol-gel matrix, with or without being removed from the mould, after the generation of the mesopores, to form a dry sol-gel matrix. The drying step may be carried out under a stream of air or an inert gas, in particular molecular nitrogen, argon or carbon dioxide, helium, indeed even molecular oxygen or molecular hydrogen.
[0031] The formation of the porous monolith may include a heat treatment of the sol-gel matrix or matrices, with or without being removed from the mold or molds, in particular after drying. The heat treatment may be carried out by stepwise heating in a closed container under a flow of air or an inert gas, in particular molecular nitrogen, argon or carbon dioxide, helium, indeed even molecular oxygen or molecular hydrogen, followed by maintaining the final temperature for a given time. The stepwise heating may be an increment of 0.5°C / min until a temperature equal to or greater than 300°C, more preferably equal to or greater than 340°C, for example substantially equal to 350°C, is reached to obtain a porous monolith. The final temperature may be maintained for more than 1 hour. This allows to stabilize the structure of the monolith and to remove organic residues resulting from the synthesis.
[0032] In an alternative form, the porous monolith is formed directly in the mold into which the sol is inserted and removed therefrom, particularly by the methods described above.
[0033] <Porous monolith> The porous monolith may comprise macropores, in particular macropores with dimensions of 50 nm or more. The macropores may present dimensions of 30 μm or less. The porous monolith may comprise mesopores, in particular with dimensions of 50 nm or less, more preferably between 2 and 50 nm. Preferably, the pores are interconnected in the porous monolith. This makes it possible to obtain porous monoliths with hierarchical porosity, i.e. exhibiting pores of at least two orders of magnitude in size, preferably macropores formed during the formation of the sol-gel matrix, and mesopores formed during the controlled generation of the mesopores. Such a porous monolith exhibits a good surface area for exchange between the solution crossing it and the material, minimizing the distances traveled by diffusion. Moreover, this makes it possible to introduce flexibility into the sol-gel matrix while reducing the risk of breakage. Furthermore, this makes it possible to reduce the drying time of the sol-gel matrix.
[0034] The porous monolith may exhibit a maximum dimension transverse to the conduit of less than 2mm, more preferably less than 1.5mm, even more preferably less than 1mm.
[0035] A free-standing porous monolith may exhibit a maximum dimension transverse to the conduit of 20 μm or greater.
[0036] Preferably, the porous monolith may exhibit a length of at least 0.5 mm, more preferably at least 1 mm, even more preferably at least 2 mm.
[0037] Preferably, the porous monolith may exhibit a length taken along the longitudinal axis of the conduit that is greater than its greatest transverse dimension.
[0038] Preferably, the porous monolith is incorporated into a conduit and configured such that liquid traversing the fluid conduit traverses the porous monolith over a distance of at least 10% of its length, more preferably at least 50%, even more preferably the entire length.
[0039] Preferably, the porous monolith is cylindrical with a diameter of 1.5mm or less, more preferably 1mm or less, and a length of 0.5mm or more, more preferably 1mm or more, even more preferably 2mm or more.
[0040] The porous monolith may be of substantially homogeneous structure throughout its volume.
[0041] The porous monolith may exhibit an aspect ratio, defined as the ratio of its height to its largest transverse dimension, of 0.2 or more, more preferably 0.4 or more, more preferably 1 or more, and / or 1000 or less, more preferably 500 or less, even more preferably 100 or less, more preferably 50 or less, even more preferably 20 or less.
[0042] Preferably, the porous monolith is cylindrical, in particular a cylinder of revolution, with a polygonal, elliptical or circular base.
[0043] The method may also include modification of the porous monolith after its manufacture, in particular functionalization of the surface of the porous monolith, in particular before or after its incorporation into the conduit. The surface of the porous monolith may be covered with hydrophobic hydrocarbon ligands, such as octadecyl ligands, or hydrophilic ligands, such as molecules of 2,3-dihydroxypropyl derivatives. The ligands of such modified columns may be further modified using known procedures. Porous catalyst or enzyme supports may be prepared by adding enzymes, such as glucose isomerase or peptide-N-glycosidase F (PNGase F), or catalytic metal elements, such as platinum and palladium.
[0044] <Fluid conduit> Preferably, the fluid conduit exhibits at least one open end, more preferably two open ends.
[0045] Preferably, the fluid conduit traverses (transverses) the porous monolith. The fluid conduit is preferably open on both sides.
[0046] In an alternative form, the fluid conduit is closed at the downstream end of the porous monolith to form a well. In this case, the porous monolith may be at the closed end of the conduit, or the fluid conduit may include a space between its closed end and the porous monolith. During passage through the porous monolith, the sample may traverse the porous monolith from side to side, especially if a space exists downstream of the porous monolith, or traverse part of its height as it shuttles back and forth, especially if the porous monolith is at the closed end of the conduit.
[0047] Preferably, the fluid conduit is single layer.
[0048] The fluid conduit may be made from a heat shrinkable polymer, in particular a polyolefin such as polyethylene (PE) or polyvinyl chloride (PVC), polytetrafluoroethylene (PTFE), fluorinated ethylene-propylene (FEP), polyetheretherketone (PEEK), or polyvinylidene fluoride (PVDF), or mixtures thereof.
[0049] The fluid conduit may exhibit a constant wall thickness of at least 0.004 mm, more preferably at least 0.15 mm, even more preferably at least 0.2 mm. Preferably, the wall thickness of the conduit is no more than 1 mm, more preferably no more than 0.9 mm, even more preferably no more than 0.65 mm.
[0050] The fluid conduits may be rigid, flexible, or preferably semi-rigid.
[0051] The fluid conduit may have an elastic wall.
[0052] The fluid conduits may be transparent, which allows direct visualization of the passage of solutions, particularly if the solutions are colored, thereby allowing monitoring of the process.
[0053] In an alternative form, the conduit may be completely or at least partially opaque. The conduit may comprise a transparent viewing window in the porous monolith.
[0054] Preferably, the fluid conduit is configured such that after incorporation of the porous monolith, it exhibits a minimum diameter that is less than or equal to, more preferably strictly less than, the maximum transverse dimension of the porous monolith, preferably the minimum transverse dimension of the porous monolith, in particular its diameter, the transverse dimension being taken along a cross-section of the conduit after incorporation of the monolith into the conduit. The fluid conduit may comprise a minimum diameter that is strictly less than 100%, more preferably less than or equal to 98%, even more preferably less than or equal to 95% of the minimum transverse dimension of the porous monolith, in particular its diameter. The minimum diameter of the conduit may be more than 50%, more preferably 60%, more preferably 70%, more preferably 80% of the minimum transverse dimension of the porous monolith.
[0055] The fluid conduit may exhibit a contraction factor, defined as the ratio of initial diameter to the minimum diameter achievable after contraction, of 1.5:1 or more (1.5:1 or more), more preferably 2:1 or more (2:1 or more). Preferably, the contraction factor is 6:1 or less (6:1 or less).
[0056] The fluid conduit may be configured to shrink at a temperature of 70°C or greater, more preferably 100°C or greater.
[0057] In an alternative form, the fluid conduit may be a pipette tip or a solid phase extraction cartridge. In this case, the porous monolith may be forcefully inserted into the fluid conduit. The fluid conduit may include an inner wall presenting an airtight layer in contact with the outer wall of the porous monolith. Such a layer may be made from an adhesive layer or a layer made of an elastic material. The fluid conduit may present an inner diameter equal to or less than the inner diameter of the porous monolith. In this case, the fluid conduit and the porous monolith may be of complementary conical shape. Preferably, at least a part of the conduit, having a length equal to or greater than the length of the porous monolith, and more preferably the entire conduit, is a cylindrical tube, in particular in the form of a circular bottom. In an alternative form, at least a part of the conduit, having a length equal to or greater than the length of the porous monolith, and more preferably the entire conduit, is in the form of a truncated cone. The term "length of the porous monolith" is understood to mean its maximum dimension along the longitudinal axis of the conduit after integration. Preferably, the porous monolith has an outer surface of the same shape as said part of the conduit, except for the dimensions, if appropriate.
[0058] Preferably, the fluid conduit, after the incorporation of the porous monolith, exhibits a fluid transfer length strictly greater than the length of the porous monolith. Preferably, the fluid conduit, at its open end or at one of its open ends, exhibits a non-zero length of conduit without the porous monolith after the incorporation of the porous monolith. This allows facilitating the introduction of the sample into the tube upstream of the porous monolith by facilitating the incorporation of the assembly into the extraction device due to the ease of fluid connection of the extended end. Furthermore, the length of fluid transfer can be adapted depending on the specific fluidic protocol of the specific use case.
[0059] Preferably, the porous monolith is integrated into the fluid conduit without protruding from the fluid conduit, which allows for easy integration of the fluid conduit into a fluidic device and facilitates the passage of a liquid sample through the fluid conduit, and in particular allows for the provision of liquid in the fluid conduit upstream of the porous monolith, thereby allowing a volume of solution or a sequence of predetermined volumes of solutions to be pre-primed in the fluid conduit upstream of the porous monolith and passed through the porous monolith.
[0060] <Incorporation stage> Preferably, the fluid conduit exhibits one or more open ends prior to incorporation of the porous monolith, and the open end or at least one of the open ends of the fluid conduit prior to incorporation remains open during incorporation of the porous monolith, allowing a sample to be passed through the porous monolith without the need to open an end of the conduit after incorporation of the porous monolith.
[0061] Preferably, the porous monolith retains its integrity during the step of incorporation into the fluid conduit. In particular, the incorporation of the porous monolith into the fluid conduit is carried out in such a way that it is not necessary to cut off a part of the porous monolith, in particular one of its ends, in order to allow the passage of the sample therein. This makes it possible to limit the risk of degradation of the porous monolith by limiting the action on it, and makes it easier to incorporate the assembly of the fluid conduit incorporating the porous monolith into a device for the transfer of samples. In particular, in the step of incorporation, the fluid conduit is not melted in order to encapsulate the porous monolith. Such incorporation requires cutting the porous monolith at least at one end of the porous monolith over the penetration thickness in order to generate a local penetration of the material of the fluid conduit at the surface of the porous monolith, thereby allowing the passage of the sample, which may damage the porous monolith, in particular in the case of small diameters.
[0062] Preferably, the incorporation of the porous monolith is performed without the need to cut a portion of the length of the fluid conduit to allow the passage of the sample through the porous monolith. The resulting device allows for limiting the steps required before one or more solutions, particularly the sample, pass through the fluid conduit.
[0063] Preferably, the fluid conduit is made from a heat shrinkable polymer and incorporating the porous monolith into the fluid conduit may comprise inserting the porous monolith into the fluid conduit and heating the fluid conduit to shrink the conduit so as to enclose the porous monolith in said conduit.
[0064] Preferably, the heating of the conduit is carried out at a temperature above the minimum shrinkage temperature of the conduit, in particular at a temperature above 70° C., more preferably at least 100° C., even more preferably at least 300° C. Preferably, the heating of the conduit is carried out at a temperature below the melting or degradation temperature of the fluid conduit, in particular at a temperature below 800° C., preferably at most 700° C., more preferably at most 500° C.
[0065] Preferably, the shrinkage of the conduit is such that after shrinkage, the inner wall of the conduit extends into the surface pores of the porous monolith and along the coated surface of the porous monolith without melting.
[0066] Preferably, the contraction of the conduit is such that the porous monolith remains fixed within the conduit when the solution is introduced into the tube at a pressure of between 0.05 and 7 bar, preferentially between 0.1 and 5 bar, and even more preferably between 0.15 and 4 bar.
[0067] Preferably, heating of the conduit is effected by heating the conduit over at least a portion of the length of the porous monolith, more preferably over the entire length of the porous monolith, for a time and temperature selected such that the fluid conduit shrinks, in particular until it conforms to the shape of the coating surface of the porous monolith and until it contacts the outer wall of the porous monolith. Preferably, after heating, the portions of the conduit immediately upstream and downstream of the porous monolith exhibit respective diameters strictly less than 100%, more preferably 95% or less, more preferably 90% of the smallest transverse dimension of the immediately adjacent ends of the porous monolith.
[0068] Heating of the conduit may be performed using a heating gun that is manually moved along the conduit. Preferably, the heating gun is moved along the conduit in a substantially regular manner so as not to heat the conduit section for longer than 10 minutes, more preferably longer than 2 minutes, even more preferably longer than 1 minute. The heating gun may be adjusted to emit a temperature of greater than 450° C. at the outlet during heating of the conduit, and may be positioned less than 15 cm, more preferably less than 4 cm, even more preferably 2 cm from the conduit during heating.
[0069] In an alternative embodiment, the heating is performed in an oven. In this case, the temperature of the oven is at least 70°C, more preferably 150°C or more, even more preferably 300°C or more, preferably 800°C or less, more preferably 700°C or less, even more preferably 500°C or less. Preferably, the temperature is selected between the minimum shrinkage temperature and the melting or degradation temperature of the fluid conduit. The heating may be maintained for a time depending on the temperature, in particular for temperatures between 300°C and 450°C for up to 1 hour, and for temperatures between 450°C and 650°C for up to 30 minutes, more preferably 15 minutes, so as not to degrade the heat-shrinkable polymer of the fluid conduit.
[0070] Preferably, the assembly of conduit and porous monolith after incorporation is characterized in that it does not contain a continuous fluid pathway extending between the inner wall of the conduit and the porous monolith connecting the conduit portions over a length at least 20 times greater than the average size of the macropores, more preferably over a length at least 10 times greater than the average size of the macropores.
[0071] In an alternative embodiment, the heating step may be performed according to a predetermined variable temperature profile. The predetermined temperature profile may include a temperature stationary phase and / or an increasing temperature gradient.
[0072] The method may include incorporating a plurality of porous monoliths into a plurality of unconnected conduits, and passing a plurality of samples through the porous monoliths, each in one of the conduits.
[0073] The porous monolith may be configured such that during passage of a sample through the fluid conduit, all of the fraction of the sample travels through the porous monolith over at least a portion of the length of the porous monolith.
[0074] After incorporating the porous monolith into a fluid conduit, the fluid conduit may be incorporated into a fluidic device configured to introduce and move solutions, particularly samples, through the conduit.
[0075] The fluidic device may include a solution feed member configured to be connected to an end of a fluid conduit, the other end of which may be configured to be connected to an interchangeable liquid reservoir depending on the solution introduced into the conduit, in particular a reservoir containing a sample.
[0076] The fluidic device may include a pressure controller or syringe driver connected to a fluid conduit upstream or downstream of the porous monolith, particularly via a liquid feed member of the conduit, and configured to control the movement of fluid through the conduit.
[0077] In an alternative form, the device may comprise a centrifugation device for forcing the solution, in particular the sample, through the porous monolith by centrifugal force, in particular when the conduit presents a closed end.
[0078] The conduit may be open at both of its ends and the fluidic device may include a member for distributing the liquid at the outlet of the fluid conduit. The member for distributing the liquid may be a needle. Such a member for distributing the liquid may facilitate the accuracy of collection of the liquid at the outlet of the conduit and the accuracy of distribution on or in the collection member or members. In an alternative form, the solution at the outlet of the conduit is collected directly without passing through an additional distribution member at the outlet of the conduit.
[0079] <Sample> Preferably, the sample passing through the porous monolith is less than 500 μl, more preferably less than 250 μl, even more preferably less than 100 μl.
[0080] The sample may be formed from a collected sample of blood, in particular plasma or serum, cerebrospinal fluid, urine, or breast milk, in particular human breast milk. Preferably, such a collected sample is modified (denatured) before passing through the porous monolith.
[0081] <Solid phase extraction> The method may be a method of solid phase extraction of a compound of interest by adsorbing it onto the surface of the porous monolith, separating it from the remainder of the sample, and then recovering the compound of interest adsorbed onto the surface of the porous monolith by elution. The method preferentially comprises conditioning the porous monolith by passing one or more successive conditioning solutions in a fluid conduit through the porous monolith before passing the sample. Such conditioning allows the porous monolith to be impregnated with a solvent to improve the adsorption of the compound of interest. The conditioning of the porous monolith in the conduit may comprise the passage of a polar solvent, in particular comprising water and / or acetonitrile. Preferably, the polar conditioning solvent is the same as the solvent of the sample. The conditioning may comprise passing a first solution of water, in particular pure water, through the porous monolith in the conduit, and in particular an 80% by volume aqueous solution of acetonitrile.
[0082] The method may include washing the porous monolith after passing the sample through it by passing one or more washing solutions through the porous monolith in a fluid conduit. The washing solutions may be less polar than the solvent of the sample. The washing solutions may be more than 50% by volume, more preferably 70% acetonitrile in water. Such washing may remove impurities from the porous monolith without eluting the compounds of interest, improving the purity of the analyte.
[0083] The method may comprise, after passing the sample and, if appropriate, after washing, elution of the compound of interest by passing the elution solution or several fractions of the elution solution through a porous monolith in a fluid conduit, and recovery of the eluates intended for analysis, in particular to determine the composition of the compound of interest. The elution may be carried out by passing several successive fractions of the elution solution through a porous monolith, whether unconnected or not, and recovering each eluate after passing through the porous monolith in a separate recovery system. The fraction or each fraction of the elution solution may exhibit a volume of 10 μl or less, more preferably 5 μl or less, even more preferably 1 μl or less. The recovery of the eluates may be carried out in different areas of a plate, in particular a mass spectrometer plate using a matrix-assisted laser desorption / ionization (MALDI) source coupled or not to a time-of-flight analyzer (MALDI-TOF).
[0084] The method may include analysis of the elution solution, which may be more polar than the solvent of the sample, in particular pure water.
[0085] The analysis may be carried out by mass spectrometry, in particular a mass spectrometer coupled with a matrix-assisted laser desorption / ionization (MALDI) source and a time-of-flight (TOF) analyzer, liquid chromatography coupled with detection by fluorescence (LC-Fluo) or capillary electrophoresis coupled with fluorescence (CE-LIF). The analysis is preferably carried out without a prior step of drying the eluted solution after collecting the eluted solution and adding a matrix substance suitable for the optional analytical method, in particular MALDI-TOF, in particular a solution comprising 2,5-dihydroxybenzoic acid in 50% by volume of methanol.
[0086] Preferably, the extraction method is carried out in the absence of an acid, in particular formic acid or trifluoroacetic acid. In an alternative form, an acid, in particular an acid, in particular formic acid or trifluoroacetic acid, in a proportion of 0.1% by volume or more is added to the conditioning solution, the washing solution and / or the elution solution.
[0087] A base may be added to the conditioning solution, the washing solution and / or the elution solution.
[0088] Preferably, this extraction method includes a preliminary step of preparing, in a fluid conduit upstream of the porous monolith, a sequence of different successive solutions, in particular conditioning solution, sample, washing solution and elution solution, in the form of one or more successive fractions, which must pass through the porous monolith to allow extraction. This allows precise control of the extraction by simple control of the pressure in the fluid conduit. This also allows precise control of the volumes of the different solutions and the times between the different stages.
[0089] The method may comprise a single pass of the sample and / or the (various) solutions through the porous monolith, where the sample and / or solutions preferentially traverse the porous monolith over its entire length, the conduit being preferentially open on both sides of the porous monolith or exhibiting a free space downstream of the porous monolith.
[0090] In an alternative form, the method may comprise passing the sample and / or the (various) solutions through part or all of the length of the porous monolith more than once. Thus, the sample and / or the (various) solutions may pass through part or all of the porous monolith one or more times. This is particularly true when the porous monolith is at the bottom of a closed conduit.
[0091] Preferably, the passage of the sample and / or the (various) solutions through the porous monolith is driven, in particular by controlling the pressure in the fluid conduit, or by any other means, in particular by application of centrifugal force. In an alternative form, the passage of the sample and / or the (various) solutions through the porous monolith may be driven by gravity.
[0092] In particular, in the case of a porous monolith integrated into the bottom of a fluid conduit having one of its ends closed, the method may include agitation of the fluid conduit during each of the above steps of passing a solution through the porous monolith, to allow movement of the solution and / or sample present in the porous monolith.
[0093] The method may be a method for extracting free N-glycans or oligosaccharides in a biological sample.
[0094] Preferably, the sample passed through the porous monolith comprises free N-glycans or oligosaccharides, and the porous monolith is configured to adsorb these entities contained in the sample as the sample passes through the porous monolith.
[0095] The method may also include preparing the sample prior to extraction, in particular the release of N-glycans or oligosaccharides in the sample. In the case of extraction of N-glycans, the sample may be prepared prior to extraction according to the method described in the paper by Sophie Cholet et al., N-Glycomics and N-Glycoproteomics of Human Cerebrospinal Fluid, Current Proteomic Approaches Applied to Brain Function, 127, Humana Press, 360 p., 2017, Neuromethods, 978-1-4939-7119-0 978-1-4939-7118-3. The preparation of the sample may include the following steps, in particular as described in the above paper: - denaturation of glycoproteins to release N-glycans, followed by enzymatic deglycosylation of the proteins and conversion of the residual glycosylamines in the solution obtained after deglycosylation of the proteins into glycans, - derivatization by permethylation as described in the above mentioned paper by Sophie Cholet et al. or, even more preferably, ethyl esterification of the sialic acids of the N-glycans of the solution obtained after deglycosylation as described in the paper by Reiding et al., Anal.Chem., 86, 5784-5793 (2014), High-Throughput Profiling of Protein N-Glycosylation by MALDI-TOF-MS Employing Linkage-Specific Sialic Acid Esterification.
[0096] The method may include adding a polar solvent to the sample before it is passed through the porous monolith, in particular an aqueous polar solvent of 80% acetonitrile.
[0097] <Reusability (recyclability)> The method may include recycling the porous material by heat treatment. The heat treatment may be carried out while the porous monolith is retained in the fluid conduit. In an alternative embodiment, the heat treatment for recycling is carried out after removing the porous monolith from the fluid conduit. The heat treatment may be carried out by heating the porous monolith at a temperature of at least 100°C, more preferably at least 150°C, even more preferably at least 200°C, for a period of at least 0.5 hours, even more preferably at least 1 hour.
[0098] The method may include re-use of the porous monolith after recycling.
[0099] <Enclosure method> According to another aspect, another subject of the invention is a method for incorporating a free-standing porous monolith in a heat-shrinkable conduit, in particular made of a polymer, comprising the following steps: - incorporating the porous monolith into a conduit; - shrinking the conduit by heating it according to a predetermined temperature profile over time, the temperature profile over time being configured such that the porous monolith is held stationary within the conduit and a force applied to the free-standing porous monolith is less than a critical resistance force of a test porous monolith manufactured by the same method as the free-standing porous monolith, of the same length as the free-standing porous monolith, and having a maximum transverse dimension of 3 mm or less. The method includes:
[0100] The term "limiting resistance force possessed by the porous monolith" is understood to mean a force that must not be exceeded in order not to damage the porous monolith.
[0101] Such an encapsulation method allows for encapsulation of all sizes of porous monoliths, especially those with diameters less than 3 mm, without damage.
[0102] Preferably, the porous monolith exhibits a maximum dimension transverse to the conduit of not more than 3 mm, more preferably not more than 2 mm, even more preferably not more than 1.5 mm.
[0103] The characteristics of the porous monolith, fluid conduits, and methods for incorporating the porous monolith described above apply regardless of the extraction method.
[0104] Another subject of the present invention is a method for solid phase extraction of one or more compounds of interest from a liquid sample, comprising the following steps: - incorporating a free-standing porous monolith into a fluid conduit such as according to the previously described aspects of the invention; - passing the sample at least once through the porous monolith within the fluid conduit; The method includes:
[0105] The properties discussed above in relation to the previously described extraction methods apply regardless of the extraction method.
[0106] <Glycomics analysis method> The present invention also relates to a method for the glycomic analysis of a sample containing N-glycans, comprising the steps of: - passing the sample at least once through the preconditioned porous monolith to adsorb N-glycans of the sample, the porous monolith being integrated within a conduit of a fluidic device; - washing the porous monolith by passing a washing solution through the porous monolith; - eluting the N-glycans by passing an elution solution through the porous monolith; - collecting the eluate at the outlet of the porous monolith; - A step of subjecting the collected elution solution to glycomics analysis. The present invention relates to a method comprising the steps of:
[0107] The properties mentioned above in relation to the extraction methods described above apply independently of said extraction method, where they are suitable. [Brief description of the drawings]
[0108] [Figure 1] FIG. 1 diagrammatically represents an example of an extraction device making it possible to carry out the extraction method according to the invention. [Diagram 2] FIG. 2 is a cross-sectional view along II-II of the assembly of the conduit of FIG. 1 and the porous monolith incorporated therein. [Diagram 3] FIG. 3 is a detailed view taken along line III in FIG. [Figure 4] FIG. 4 shows a diagram illustrating a method for producing a porous monolith making it possible to carry out the method according to the invention. [Diagram 5] FIG. 5 is a diagram representing the different stages of a solid phase extraction method according to the invention. [Figure 6] FIG. 6 illustrates the stage of collecting the elution solution at the outlet of the conduit after carrying out the extraction method. [Figure 7] FIG. 7 is a diagram depicting an alternative form of the solid phase extraction method. [Figure 8]FIG. 8 depicts an alternative form of extraction device. [Figure 9] FIG. 9 is a diagram depicting an alternative form of the solid phase extraction method. [Figure 10] FIG. 10 depicts an alternative form of extraction device. [Figure 11] FIG. 11 depicts an alternative form of extraction device. [Figure 12] FIG. 12 shows a spectrum of N-glycans obtained from human plasma obtained from the elution fraction at the outlet of the conduit after carrying out the method according to the present invention, with mass-to-charge ratios (m / z) of identified molecules of 1000 to 5000 Da. [Figure 13] FIG. 13 shows the spectrum of the N-glycans of FIG. 6 with m / z ratios between 1100 and 2000 Da. [Figure 14] FIG. 14 shows the spectra of the N-glycans of FIG. 6 with m / z ratios of 2000 to 3500 Da. [Figure 15] FIG. 15 shows the spectrum of the N-glycans of FIG. 6 with m / z ratios of 3400 to 4500 Da. [Figure 16] FIG. 16 represents two spectra obtained with the same extraction method according to the invention on the same sample, before and after reuse of the porous monolith. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0109] A device 10 for carrying out an extraction method according to the invention is shown in Figure 1. The device 10 comprises a porous monolith 20 embedded in a fluid conduit 30 such that liquid traversing the fluid conduit from side to side of the porous monolith 20 passes through the porous monolith 20, with the porous monolith 20 acting as a filter within the conduit 30.
[0110] The conduit is connected at one of its ends to a liquid feed member 40 of the conduit, which may be removably connected to a liquid reservoir 50. The feed member 40 may also be connected to a pressure controller, which allows to control the pressure in the fluid conduit and thus to control the fluid movement in the fluid conduit. The other end of the conduit may be free. However, the invention is not limited to the free end. The free end may be connected to a needle-shaped member for dispensing liquid. Such a free end allows the solution moving at the outlet to be deposited in the extraction support 60, in particular in a receptacle, in particular an analysis well or a MALDI plate for its analysis by an auxiliary device such as a MALDI-TOF, or in a receptacle 62, in particular a removal receptacle for collecting the various solutions removed during the method.
[0111] The porous monolith 20 and conduit 30 are cylindrical in the illustrated embodiment, but may be other, and although a cylindrical shape is preferred, the invention is not limited to any particular shape.
[0112] The porous monolith 20 has a hierarchical porosity exhibiting macropores and mesopores and exhibits a diameter less than or equal to 3 mm, in this example substantially equal to 1 mm.
[0113] The various stages of an example of a method for producing a porous monolith are shown in FIG.
[0114] The method comprises a first step, not shown, of the formation of an aqueous solution of pore-forming agents and sol-gel precursors, and optionally additives, in particular acids and / or agents for dissolving the matrix.
[0115] The pore-forming agent may be selected from water-soluble polymers, in particular polyethylene glycol (PEG), poly(acrylic acid), sodium poly(styrenesulfonate) acid, and poly(ethyleneimine).
[0116] The water-soluble polymer may exhibit a molecular weight of 1000 to 100000 daltons, preferably 5000 to 50000 daltons, and even more preferably 5000 to 30000 daltons.
[0117] The concentration of the pore former, in particular PEG, may be between 0.015 g and 0.35 g per ml of sol, preferentially between 0.02 g and 0.2 g per ml of sol. These values relate to the concentration of the sol-gel precursor, in particular tetramethoxysilane (TMOS), with values of 0.03 to 1 g of pore former, in particular PEG, per ml of sol-gel precursor, in particular tetramethoxysilane (TMOS), preferentially between 0.06 to 0.6 g of pore former, in particular PEG, per ml of sol-gel precursor, in particular tetramethoxysilane (TMOS). This is chosen as a function of the size of the macropores desired for the final porous monolith.
[0118] The sol-gel precursor may be selected from alkoxides, in particular hydrolyzable and condensable organometallic compounds, in particular zirconium alkoxides, in particular zirconium butoxide (TBOZ), zirconium propoxide (TPOZ), titanium, niobium, vanadium, yttrium, cerium, aluminium or silicon alkoxides, in particular tetramethoxysilane (TMOS), tetraethoxysilane (TEOS), tetrapropoxysilane (TPOS), tetrabutoxysilane (TBOS), trimethoxysilanes, in particular methyltrimethoxysilane (MTMOS), propyltrimethoxysilane (PTMOS) and ethyltrimethoxysilane (ETMOS), triethoxysilanes, in particular methyltriethoxysilane (MTEOS), ethyltriethoxysilane (ETEOS), propyltriethoxysilane (PTEOS), aminopropyltriethoxysilane (APTES) and mixtures thereof, for example TMOS. Also precursors such as sodium silicate or titanium colloids can be used, especially if the purity requirements allow, i.e. are not too high.
[0119] The percentage of pore former in the sol and the percentage of sol-gel precursor in the sol are predetermined as a function of the properties of a selected sample of a known sol-gel matrix taken immediately after gelation, in particular the total porosity and the average size of the macropores.
[0120] The solution is then stirred for a predetermined time period ranging from 5 minutes to 3 hours, and even more preferably from 15 minutes to 2 hours, at a substantially constant and controlled temperature between 0° C. and 90° C., and more preferably between 0° C. and 50° C. This stirring step allows the sol-gel process to begin before phase separation to form sol 5.
[0121] Sol 5 is then added in step 2 to the receptacle 12 to at least partially fill said receptacle 12 and at least one mold 15 contained within the chamber 12 .
[0122] The mold 15 may be positioned in a chamber that is gradually filled with the sol 5, so that the mold 15 fills gradually without the presence of air bubbles or chemical composition gradients. Filling can be performed until the mold 15 is completely immersed. Partial immersion is also possible. Throwing of the mold into the sol 5 contained in the chamber 12 is also possible.
[0123] The chamber 12 may be configured to contain multiple identical or different molds 15. The chamber 12 may be cylindrical as shown, or may have other shapes. The chamber 12 may be made of plastic, particularly PTFE, PP, PE, PC, PET, PVC, or glass, or stainless steel.
[0124] The mold 15 comprises two openings 17 and 18 on opposite faces of the mold 15, at least one of the two openings 17 extending below the sol level after filling. Such openings allow filling of the chamber 12 containing the mold 15, or at least partial immersion of the mold 15 in the sol 5 contained in the chamber 12 and the transfer of the sol 5 between the interior and exterior of the mold before it is fully condensed. In the example shown, the mold 15 is in the form of a tube open at two ends and extending vertically in the chamber 12, but the situation may be quite different. The tube may be oriented in the chamber in a different manner and / or the mold may have another shape.
[0125] The mold 15 may be completely contained within the chamber 12 as shown, or may protrude from the chamber 12. In the first case, the mold 15 may or may not be completely immersed in the sol 5 after filling.
[0126] The mould 15 may be made from plastic, in particular PTFE, PEEK, FEP, PE, PP or polylactic acid, or glass, or stainless steel, in particular borosilicate, or fused silica.
[0127] The mould may be in a porous body.
[0128] The mold may be formed by 3D printing or molding.
[0129] The maximum transverse dimension of the cavity of the mould 15, in particular the diameter d of this cavity, may be between 13 mm and 0.025 mm.
[0130] Once the sol 5 is introduced into the chamber 12 and mold 15, condensation takes place in the chamber and mold assembly in step 3. This sol-gel transition can be followed by at least partial maturation (or aging) of the assembly, which ensures the formation of homogeneous macropores of similar nature in the formed sol-gel matrix 22, regardless of their shape and their size.
[0131] During the condensation, the temperature may be kept substantially constant, in particular between 15° C. and 90° C., preferentially between 25° C. and 70° C., for a period of time ranging from 10 minutes to 4 hours. The duration of the condensation and the predetermined temperature depend on the desired internal structure of the sol-gel matrix and on the duration of the stirring of the initial solution during the formation of the sol.
[0132] The at least partial ageing may last from 30 minutes to 2 weeks, in particular less than 72 hours, at ambient temperature. Preferably, the duration of ageing is short enough to prevent the formation of mesopores and / or micropores.
[0133] The block 22 of sol-gel matrix containing the mold 15 is then removed from the chamber 12 in step 4. If the mold 15 is only partially immersed, this step may be optional, as will be seen later.
[0134] The mold 15 and the sol-gel matrix 25 it contains are then removed from the porous solid in step 5, for example by cutting the sol-gel matrix of the block 22 flush with the mold and then extracting the mold 15 and the sol-gel matrix 25 it contains, or by breaking the sol-gel matrix of the block 22 around the mold 15. If the immersion was partial, it is possible to extract the mold 15 and the sol-gel matrix 25 it contains directly from the previously extracted block or directly from the chamber 12.
[0135] The sol-gel matrix 25 is then removed from the mold 15 in step 6. This is done by controlled pressure applied to the sol-gel matrix 25 while supporting the mold 15. The pressure may be obtained either by a solid made of plastic, glass, for example a capillary tube made for example of fused silica, or any other material sufficiently robust and smaller in dimensions than the mold 15, or by a controlled flow of gas. The removal operation may be facilitated by immersing the assembly of the mold 15 and the sol-gel matrix 25 in a liquid. To remove the sol-gel matrix 25, it is optionally possible to create a slight pressure difference by tapping the assembly of the mold 15 and the sol-gel matrix 25.
[0136] Once the sol-gel matrix 25 has been removed from the mold 15, the method may include a stage of controlled generation of mesoporosity. This stage may be carried out by immersing the sol-gel matrix 25 or the mold / sol-gel matrix assembly in a basic solution, for example a 1M ammonium hydroxide solution, or by heating the material in water in the presence of a precursor, for example urea, to generate ammonia in situ. It should be noted that in a second method it is possible to add more ammonium hydroxide. This operation may last for 0.5 h to 50 h, at a substantially constant predetermined temperature of the sol-gel matrix, between 30 °C and 150 °C. This stage may be carried out simultaneously, i.e. in the same bath, for several sol-gel matrices, whether they originate from the same block or not.
[0137] Preferably, the size of the resulting pores is 50 nm or less, more preferably 2 to 50 nm.
[0138] The sol-gel matrix obtained is then dried. To do this, the sol-gel matrix is placed in a closed container, in particular an autoclave, and dried under critical or supercritical conditions, in particular under a stream of air or inert gas, in particular molecular nitrogen (N2), for a period of 10 to 20 hours. The sol-gel matrix is then subjected to a ramp of 0.5°C / min up to 350°C and a stationary phase at this last temperature for several hours under a stream of inert gas (other gases may also be utilized).
[0139] In this way, a free-standing monolith is obtained that is ready for use.
[0140] The resulting porous monolith preferably comprises macropores, ie macropores exhibiting a selected dimension greater than or equal to 50 nm, and mesopores, ie mesopores exhibiting a selected dimension between 2 and 50 nm.
[0141] Preferentially, the porous monolith is of substantially homogeneous structure throughout its volume, as can be seen in FIG.
[0142] The porous monolith may exhibit an aspect ratio, defined as its height to its largest transverse dimension, of 0.2-100.
[0143] The method may also include post-production modifications to the porous monolith, in particular functionalization of the internal surface of the porous monolith, which may be carried out according to liquid or gas phase methods using organosilanes, in particular chlorosilanes (e.g. octadecyltrichlorosilane) and alkoxysilanes (octadecyltriethoxysilane, aminopropyltriethoxysilane, propyltrimethoxysilane) or even hexadimethylsilazane.
[0144] In an alternative form, the mold may have only one opening, which opens into the sol after filling and allows movement of the sol between the mold and the chamber.
[0145] In an alternative form, the initial solution may be an emulsion or template solution containing the sol-gel precursors.
[0146] The resulting porous monolith 20 from this process is free-standing and may be incorporated within a heat-shrinkable conduit 30 .
[0147] The fluid conduit is semi-rigid and heat shrinkable. Before shrinkage, the fluid conduit exhibits an inner diameter larger than the outer diameter of the porous monolith, and after shrinkage, the fluid conduit exhibits an inner diameter smaller than the outer diameter of the porous monolith. Preferably, the minimum diameter of the conduit is strictly smaller than the diameter of the porous monolith. The minimum diameter of the conduit may be 95% to 85% of the diameter of the porous monolith.
[0148] The porous monolith is incorporated into the conduit by inserting it into the conduit before shrinking and then heating the conduit to a temperature depending on the heat shrinkable material, in particular 70°C or higher, whereby the conduit shrinks onto the porous monolith without damaging it until its diameter narrows so that the porous monolith is fixedly enclosed and liquid solution traversing the conduit passes through the porous monolith, i.e. there is no space between the inner wall of the conduit and the outer wall of the porous monolith, as can be seen in Figures 2 and 3.
[0149] Also, several porous monoliths can be integrated in parallel in order to process several samples or several fractions of a sample.
[0150] Next, a method for solid phase extraction (SPE) of a compound of interest from a sample is described.
[0151] The method comprises passing different successive solutions through the porous monolith that allow the extraction of the compounds of interest. All successive solutions may be pre-inserted at the conduit head, i.e. upstream of the porous monolith.
[0152] The extraction method may first include a conditioning step by passing a conditioning solution 200 through the porous monolith 20. This makes it possible to prepare the porous monolith for adsorption of the compounds of interest by impregnating it with a solution having a polarity close to that of the sample. The conditioning solution 200 may be, for example, an acetonitrile-water solution containing 80% by weight of acetonitrile. The conditioning solution is removed at the outlet.
[0153] The sample 300 is then passed through the porous monolith 20. During sample passage, compounds of interest present in the porous monolith 20 are adsorbed to the surface due to the compound's higher affinity for the surface of the porous monolith than for the sample's solvent. The sample 300 may be passed once through the porous monolith. In an alternative form, the sample 300 may be passed several times by passing it back and forth through the porous monolith 20. Any sample liquid remaining at the outlet may be removed.
[0154] The porous monolith 20 is then washed with a washing solution 400 for which the compounds of interest exhibit a lower affinity than the walls of the porous monolith 20. The washing solution 400 may be a 95% by weight solution of acetonitrile in water. The washing solution 400 is removed at the outlet of the porous monolith.
[0155] Finally, as shown in FIG. 6, a series of successive fractions of the elution solution 500 are captured through the porous monolith. Each fraction of the elution solution is collected at the outlet of the porous monolith in a different spot or different well 520 of the analysis plate. The elution solution is a solution for which the compound of interest has a higher affinity, in particular pure water, so that the compound of interest is captured in a fraction of the elution solution. The various fractions of the elution solution are collected at the outlet for analysis. By analyzing the composition of the various fractions of the elution solution, it is possible to deduce therefrom the proportion of the compound of interest in the initial sample. The analysis is carried out, in particular in the case of N-glycans, for example by MALDI-TOF, LC-FLUO or CE-LIF.
[0156] In an alternative configuration shown in FIG. 7, the porous monolith 20 is enclosed within a heat shrinkable conduit 30 having a non-cylindrical shape, specifically a conical shape.
[0157] The passage of the various solutions, particularly the conditioning solution 200, the sample 300, the washing solution 400, and the elution solution 500, may be effected through the porous monolith by one or more aspiration and subsequent reversal steps, as indicated by the double arrows at each step in Figure 7. In this manner, the various solutions pass through the porous monolith 20 at least twice in one direction and then in the other. After passing through the porous monolith, the solutions to be removed are collected in removal receptacles 62, and the solutions to be analyzed are collected in analysis receptacles or wells or are directly deposited on the MALDI analysis plate 60.
[0158] In an alternative embodiment shown in Figure 8, the fluid conduit 30 after encapsulation of the porous monolith is inserted into a solid-phase extraction cartridge 80, in particular of the syringe type. The various solutions are then collected after passing through the porous monolith via an outlet nozzle 82 of the extraction cartridge 80. Such an extraction cartridge can be used as described above or below.
[0159] In an alternative embodiment shown in FIG. 9, the passage of the solutions 200, 300, 400, and 500 through the porous monolith 20 may be driven by centrifugation. The porous monolith 20 may be incorporated into an extraction cartridge, the upper end of which may be closed with a stopper 84. The conditioning solution 200 is added to the extraction cartridge 80 upstream of the porous monolith 20, and the cartridge 80 is closed by a stopper 84. The cartridge is placed above a removal receptacle 62. The assembly formed by the receptacle 62 and the cartridge 80 is centrifuged to pass the conditioning solution through the porous monolith 20 and collect it in the receptacle 62. The sample 300 and the wash solution are likewise passed through the porous monolith 20 and collected in the same or another receptacle 62. The cartridge is then inserted into the extraction receptacle 60 to collect the eluate by passing the elution solution 500 likewise through the porous monolith.
[0160] In an alternative form, shown in Fig. 10, all steps of the method may be performed using a multiwell system 900 comprising a vacuum base 910 that receives a receptacle or multiwell plate 60 and on which an extraction plate 920 is attached. The extraction plate 920 comprises a matrix of extraction cartridges 80 incorporating porous monoliths. This plate 920 is placed, depending on the step of the method, on a removal receptacle 62, not shown, for collecting the solution to be removed, or on a multiwell plate 60 that presents an extraction well 520 for each extraction cartridge, for collecting the eluate at the outlet of each cartridge. The passage of the various solutions through the porous monoliths may be driven by an air suction pump in the vacuum base 910. Such a system allows several extractions to be performed simultaneously.
[0161] In an alternative form, shown in FIG. 11, the extraction may be performed by solid-phase extraction. In this case, the porous monolith may be incorporated into a receptacle, in particular of the Eppendorf® tube type, whose ends are closed. The porous monolith may extend to the bottom of the receptacle and be fixed there. Various solutions are then added to the receptacle containing the porous monolith. The tube is stirred to promote exchange between the solutions and the porous monolith. The solutions are extracted from the receptacle, in particular by inverting the receptacle or by pipetting.
[0162] Example 1 The N-glycomics analysis of human plasma samples is detailed below.
[0163] Free-standing monoliths approximately 800 μm in diameter are produced with approximately 2 μm macropores and approximately 15 nm mesopores created by immersion in a basic solution.
[0164] A solution is prepared by mixing 0.33 g PEG and 2 ml TMOS in 4 ml 0.01 M acetic acid. The solution is stirred for 30 min at 0 °C to form a sol and transferred to a polypropylene (PP) receptacle with a PTFE tube of approximately 1 mm diameter previously positioned vertically. Filling is performed by gradually adding the sol to the chamber using a micropipette, starting from the lowest point. The amount of solution added is such that the mold is completely immersed.
[0165] The chamber is placed at a temperature of 40°C and gelation occurs 45-50 minutes after transfer into the chamber. After gelation has occurred, the gel is left to age at 40°C for 24 hours. The sol-gel matrix resulting from gelation and aging is then removed from the chamber and broken using metal clamps to recover the mold embedded within it. The monolithic sol-gel matrix encapsulated in the mold is then removed by manual pressure applied by a tube less than 1 mm in diameter. For this protocol, this pressure by the solid tube is sufficient to effect removal of the monolith and does not weaken the gel.
[0166] The obtained sol-gel matrix is quickly immersed in a 1M NH4OH solution, and at the same time, a ratio of approximately 5 is observed between the volume of the basic solution and the volume occupied by the sol-gel matrix.
[0167] The matrix obtained is then placed in an autoclave. The autoclave is placed in an oven and connected by a tube that allows the circulation of gas. The gel is then dried under N2 for 12 hours. Finally, a heat treatment is performed with a ramp of 0.5°C / min up to 350°C and a stationary phase of 2 hours at a temperature of 350°C.
[0168] The monolith, with a diameter of 0.8 mm, is placed in a heat-shrinkable PTFE tube with an inner diameter of 1.27 mm before shrinking. The length of the tube is at least 10 cm.
[0169] The assembly is then subjected to a local temperature increase at the point where the monolith is positioned, using a heating gun adjusted to a temperature of 500°C. Heat is distributed manually to the tube by a steady movement of the nozzle of the gun, during which shrinkage occurs, encapsulating the monolith. The shrinkage of the tube is monitored visually. The diameter of the PTFE after shrinkage is less than 0.7 mm. This stage may also be carried out in an oven at a temperature of 350°C for at least 10 minutes.
[0170] The tube containing the encapsulated porous monolith is ready for use. It is then connected to a pressure controller via a reservoir connector into which four vessels may be placed, one for each solution (conditioning / sample / wash / elution).
[0171] At the outlet of the device, the introduced fluids are collected in a waste container (first three stages) and, for the eluate (final stage), are directly deposited on the MALDI plate.
[0172] 34 μl of diluted plasma (containing 5 μl of collected plasma) is added to 100 mM, pH 7.4 sodium phosphate buffer (10 μl) and 10 mM dithiothreitol (5 μl), followed by heating at 95° C. for 5 min to denature the plasma glycoproteins. After cooling to ambient temperature, 2 μl of PNGase F solution (1 U / μl) is added and the proteins are deglycosylated overnight (approximately 16 h) at 37° C. Residual glycosylamines are converted to glycans by incubation with 5 μl of 1 mol / l hydrochloric acid at 37° C. for 45 min.
[0173] A 0.25 M EDC / 0.25 M HOBt mixture is prepared in ethanol as an activating agent for the ethyl esterification reaction leading to the esterification of α2,3-linked sialic acid and lactonization of α2,6-linked sialic acid.
[0174] Derivatization is performed by adding 3 μl of previously removed N-glycan sample (each equivalent to 0.3 μl of human plasma) to 20 μl of esterification reagent, respectively, followed by incubation with stirring at 350 rpm for 1 h 30 min at 37° C. Then, 50 μl of 80% ACN is added to form the extracted sample, which proceeds after 10 min to the extraction of N-glycans on a silica monolith and MALDI-TOF-MS analysis.
[0175] At each stage, the solution is loaded into a vessel and delivered to the PTFE tube containing the material by positive pressure using a pressure controller. It is also possible to proceed with negative pressure using a pressure controller. Positive and negative pressure can also be applied manually, in practice, using a syringe driver. The device is also capable of proceeding with aspiration-reversal cycles to perform purification.
[0176] The PTFE-encapsulated monolith is conditioned and equilibrated with 3 x 1 ml of pure water followed by 3 x 1 ml of 80% aqueous ACN. Then, 73 μl of the extraction sample is loaded and washed with 20 μl of 95% ACN. Finally, the N-glycans are eluted in 10 successive fractions of 1 μl of pure water. Each fraction is directly deposited on the MALDI plate using the device. It should be noted that in this protocol, trifluoroacetic acid is not used.
[0177] Add 1 μl of 2,5-DHB matrix solution (2,5-dihydroxybenzoic acid, 10 mg / ml in 50% methanol) and mix with the 1 μl fractions deposited during direct elution onto the plate. After the first crystallization, deposit 0.2 μl of ethanol to recrystallize, improving the reproducibility of results during analysis.
[0178] Finally, each spot on the MALDI plate is analyzed with a MALDI-TOF / TOF instrument, in particular a Bruker UltrafleXtreme equipped with a laser, in particular a Bruker Smartbeam-II. Regarding the acquisition conditions, mass spectrometry spectra are acquired in positive mode with a laser repetition rate of 2 kHz, an acceleration voltage of 20 kV, and an extraction time delay of 130 ns. The spectra are obtained by accumulating 5000 shots in a mass measurement window of 1100-5000 Da for plasma N-glycans and 500-5000 Da for samples of free oligosaccharides (HMOs, see Example 2) from breast milk.
[0179] Following the purification protocol for human plasma, N-glycan profiles of fractions 2-4 were obtained by mass spectrometry, with the best spectrum being obtained for the third fraction.
[0180] Calibration was performed and peaks were identified by the software of the mass spectrometry device.
[0181] The obtained spectra are shown in Figures 12 to 15. The analysis made it possible to distinguish more than 58 different compositions of plasma N-glycans, some of which are shown, which correspond to more than 81 different N-glycans due to changes in the linkage of sialic acids. Eight predominant structures were found, namely H5N4E2 (m / z 2301), H5N4E1 (m / z 1982), H5N4E1L1 (m / z 2255), H6N5E2L1 (m / z 2940), H5N4F1E1 (m / z 2128), H5N4F1E2 (m / z 2447), H6N5F1E2L1 (m / z 3086) or H6N5E2L1 (m / z 2986). The ratio of the two predominant structures commonly found, mono- and bisialylated biantennary glycans, H5N4E1 (m / z 1982) and H5N4E2 (m / z 2301), shows a 1:3 ratio.
[0182] Example 2 A cylindrical free-standing porous monolith with a diameter of 5 mm and a length of 9 mm was prepared by the same method as described in Example 1. It was assembled into a heat-shrinkable PTFE tube with a length of more than 9 mm by the assembly method of Example 1 and placed into an SPE type cartridge, as shown in FIG.
[0183] The SPE cartridge containing the encapsulated porous monolith is ready for extraction. The SPE cartridge is placed under a vacuum of -0.2 bar.
[0184] 50 μl of human breast milk was diluted, vortexed, and centrifuged at 15 kG for 30 minutes at 2° C. The supernatant was then removed and 200 μl of acetonitrile (ACN) was added to the sample before vortexing.
[0185] The SPE cartridge containing the monolith is successively conditioned and equilibrated three times with 1 ml water and then three times with 1 ml 80% ACN. The sample is then loaded and washed 12 times with 200 μl 95% ACN. Finally, elution of breast milk free oligosaccharides (HMOs) is carried out with 200 μl H2O in a 2 ml tube, which is then dried under a nitrogen stream and analyzed by mass spectrometry. The resulting spectrum is shown in Figure 16, spectrum a.
[0186] After this first extraction, the cartridge is withdrawn. The porous monolith and PTFE are heat treated for 2 hours under a nitrogen stream, initially at 40° C., then with a 210 minute ramp to a final temperature of 250° C. The treated portion is then collected and returned to the cartridge, and the previous extraction protocol is used again. The conditioning and elution fractions were collected and analyzed by mass spectrometry.
[0187] No oligosaccharides or other residual compounds were detected in the conditioning fraction of this second extraction, demonstrating sufficient regeneration of the porous monolith. For the elution fraction, a profile of free oligosaccharides was obtained. An example of the mass spectrum obtained is shown in Figure 16, spectrum b.
[0188] It can be observed that the spectra in FIG. 16 obtained by the first and second extractions, respectively, are similar, clearly indicating that the porous monolith can be used several times.
[0189] The invention is not limited to the embodiments just described.
[0190] For example, the porous monolith may have shapes other than those described, the fluidic device may be other than those described, and in particular the pressure may be controlled in other ways. [Explanation of symbols]
[0191] 5. Sol 10. Devices 12···Receptacle 12. Chamber 15. Mold 17 Opening 18...Opening 20. Porous monolith 22...Sol-gel matrix 22... Block 25...Sol-gel matrix 30...Fluid conduit 40...Liquid feed member 50...Liquid Reservoir 60...extraction support 60···MALDI analysis plate 60···Extraction receptacle 60-well multi-well plate 62···Receptacle 80 Solid Phase Extraction Cartridge 82...Outlet nozzle 84 Stopper 200···Conditioning solution 300 samples 500...Elution solution 520 wells 900 Multiwell System 910···Vacuum base 920 Extraction plate
Claims
1. 1. A method for solid phase extraction of one or more compounds of interest from a liquid sample, comprising: - incorporating the free-standing porous monolith (20) into a fluid conduit (30) such that said free-standing porous monolith (20) is fixed within said fluid conduit (30) during said method to form a filter within said fluid conduit; - passing a sample (300) through the porous monolith in the fluid conduit (30) at least once over at least a portion of the porous monolith (20); Including, the free-standing porous monolith (20) having a maximum dimension transverse to the fluid conduit (20) of 3 mm or less; A method wherein said fluid conduit has one or more open ends prior to said incorporation, and wherein the end or at least one of the ends remains open during the step in which said porous monolith is incorporated.
2. The free-standing porous monolith (20) is prepared by the following steps: - forming a sol (5) comprising a sol-gel precursor in an aqueous solution, and preferably a pore former; - at least partially filling the chamber (12) and at least one mold (15) contained within the chamber (12) with a previously formed sol, the mold (15) comprising at least one opening (17) in the sol after filling with the sol; - forming a sol-gel matrix (22) in a chamber starting from a sol, - removing the mold (15) and the sol-gel matrix (25) contained within said mold from the chamber; and - removing the sol-gel matrix (25) from the mold (15); - forming a porous monolith (20) starting from the sol-gel matrix (25) removed from the mould; The method includes the steps of:
2. The method of claim 1, wherein the formation of the sol, the sol-gel matrix, and the porous monolith is carried out by a sol-gel process.
3. 3. The method according to claim 1 or 2, wherein the porous monolith has a hierarchical porosity comprising in particular macropores, in particular macropores with dimensions of 50 nm or more, and mesopores, in particular with dimensions of 50 nm or less, more preferably between 2 and 50 nm.
4. 4. A method according to any one of claims 1 to 3, wherein the porous monolith exhibits a maximum dimension transverse to the conduit of 2 mm or less, more preferably 1.5 mm or less, even more preferably 1 mm or less.
5. 5. The method according to any one of claims 1 to 4, comprising modifying the porous monolith (20) after its manufacture, in particular functionalizing the surface of the porous monolith, in particular modifying or functionalizing the surface before or after its incorporation into the fluid conduit (30).
6. 6. The method according to any one of claims 1 to 5, wherein the fluid conduit is made from a heat-shrinkable polymer, in particular a polyolefin, such as polyethylene (PE) or polyvinyl chloride (PVC), polytetrafluoroethylene (PTFE), polyetheretherketone (PEEK), fluorinated ethylene-propylene (FEP) or polyvinylidene fluoride (PVDF) or mixtures thereof, and wherein incorporating the porous monolith (20) into the fluid conduit (30) comprises inserting the porous monolith (20) into the fluid conduit (30) and heating the fluid conduit (30) for a time and at a temperature selected such that the fluid conduit shrinks until it is in contact with the outer wall of the porous monolith, in particular over at least a portion of the length of the porous monolith, more preferably over the entire length of the porous monolith, in order to shrink the conduit so as to enclose the porous monolith in said conduit.
7. A method according to any one of claims 1 to 6, wherein the porous monolith retains its integrity during the step of incorporation into the fluid conduit.
8. A method according to any one of claims 1 to 7, wherein the heating of the conduit is carried out at a temperature which is at least the minimum shrinkage temperature of the conduit and at most the melting or degradation temperature of the fluid conduit.
9. 9. The method according to any one of claims 1 to 8, wherein the fluid conduit, after incorporation of the porous monolith, exhibits at its open end, or one of its open ends, a non-zero length of the conduit devoid of porous monolith.
10. The method according to any one of claims 1 to 9, which is a method for solid-phase extraction of a compound of interest by adsorbing the compound of interest onto the surface of a porous monolith, separating it from the remainder of the sample, and then recovering the compound of interest adsorbed onto the surface of the porous monolith by elution.
11. 11. The method of any one of claims 1 to 10, comprising conditioning the porous monolith by passing one or more successive conditioning solutions in a fluid conduit through the porous monolith prior to the passage of the sample, and / or washing the porous monolith by passing one or more washing solutions in a fluid conduit through the porous monolith after the passage of the sample in the fluid conduit.
12. 12. The method according to any one of claims 1 to 11, comprising, after passing the sample and, where appropriate, after washing, passing the elution solution or several fractions of the elution solution through a porous monolith in a fluid conduit, thereby eluting the compound of interest, and collecting the elution solution or each fraction of the elution solution after passing through the porous monolith, in particular in a separate collection system, for example in different areas of a plate, in particular a mass spectrometer plate using a matrix assisted laser desorption / ionization source coupled or not to a time-of-flight analyzer, for analysis, in particular to determine its composition of the compound of interest.
13. 13. The method according to claim 12, comprising analysis by mass spectrometry, in particular a mass spectrometer with a source of matrix-assisted laser desorption / ionization (MALDI) type coupled to a time-of-flight (TOF) analyzer, liquid chromatography coupled to detection by fluorescence (LC-Fluo) or capillary electrophoresis coupled to fluorescence (CE-LIF), after recovery of the eluted solution, without a prior step of drying or concentrating the eluted solution.
14. A method according to any one of claims 1 to 13, comprising recycling the porous material by heat treatment.
15. The sample (300) passing through the porous monolith (20) contains free N-glycans or oligosaccharides, the porous monolith being configured to adsorb these entities contained in the sample while the sample passes through the porous monolith, preferentially comprising the following steps: - washing the porous monolith (20) by passing a washing solution (400) through the porous monolith; - eluting the N-glycans by passing an elution solution (500) through the porous monolith; - collecting the eluate at the outlet of the porous monolith; - A step of subjecting the collected elution solution to glycomics analysis. The method of any one of claims 1 to 14, further comprising:
Citation Information
Patent Citations
Method of manufacturing solid-phase extraction adsorption column
JP2003166983A
Supports for solid phase extraction
US7291383B2
Wallless monolith columns for chromatography
WO2005072164A1
Methods and devices using a shrinkable support for porous monolithic materials
WO2008112702A1